Effect of zinc supplementation on production performance and udder health of peri-parturient karan fries cows under heat stress condition - Kumar, Nishant; Patel, Brijesh; Singh, S V (Indian Journal of Dairy Science, 2017)
Present study was carried out to evaluate the effect of zinc (Zn) supplementation on production performance and udder health of peri-parturient KF (Karan Fries) cows during heat stress condition. 18 peri-parturient Karan Fries cows were divided into three groups namely control, T1 and T2 having six cows in each group. Control group was fed basal diet alone, however T1 and T2 groups were fed with 80 ppm and 120 ppm Zn, respectively along with basal diet from 45 days pre-partum to 45 days post partum. Results showed that plasma Zn level was significantly (P